(untitled) (Journal of Human Sciences, 2024)
This research addresses definition of failure: its causes, and its treatment in light of the Holy Quran. The material related to (failure) has been studied within the Quranic context through an analytical and interpretive approach, aiming to define it, explain its implications, and clarify its meaning in each context. The research also explores the causes of failure and ways to treat and recover from it based on the Quranic perspective. The study consists of an introduction, a preamble, two main chapters, and a conclusion, and it employs three scientific methodologies: inductive, thematic, and analytical. It was shown through the study: the material related to (failure) appears in four instances in the Holy Quran and is mentioned in the context of disputes and differences that lead to failure and loss of strength. Furthermore, in Islam, failure is considered part of the human experience and not the end of the road; rather, it is an opportunity for learning and spiritual and moral growth .